2021
DOI: 10.3389/fpls.2021.736332
|View full text |Cite
|
Sign up to set email alerts
|

Morus alba L. Leaves – Integration of Their Transcriptome and Metabolomics Dataset: Investigating Potential Genes Involved in Flavonoid Biosynthesis at Different Harvest Times

Abstract: The mulberry leaf is a classic herb commonly used in traditional Chinese medicine. It has also been used as animal feed for livestock and its fruits have been made into a variety of food products. Traditionally, mulberry (Morus alba L.) leaf harvesting after frost is thought to have better medicinal properties, but the underlying mechanism remains largely unsolved. To elucidate the biological basis of mulberry leaves after frost, we first explored the content changes of various compounds in mulberry leaves at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In this study, we evaluated the metabolites of three typical developmental stages of the peel and kernel of gardenia using UPLC-MS/MS and explored the changes of related compounds and their respective genes at different developmental stages by transcriptome analysis. The results showed that there were significant differences in the contents of flavonoids and different expression of flavonoid biosynthetic genes at different developmental stages and in different tissues, which were consistent with the results on mulberry leaf, blueberries, Kiwifruits and sugarcane species, indicating that the metabolism of flavonoids was genetically regulated at different developmental stages and among different tissues, and their anabolic pathways are highly conserved in plants [ 32 – 35 ]. And the metabolite species were not consistent with previous studies, which may be due to the different species of gardenia, suggesting that the genotype plays a decisive role in its metabolite species [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we evaluated the metabolites of three typical developmental stages of the peel and kernel of gardenia using UPLC-MS/MS and explored the changes of related compounds and their respective genes at different developmental stages by transcriptome analysis. The results showed that there were significant differences in the contents of flavonoids and different expression of flavonoid biosynthetic genes at different developmental stages and in different tissues, which were consistent with the results on mulberry leaf, blueberries, Kiwifruits and sugarcane species, indicating that the metabolism of flavonoids was genetically regulated at different developmental stages and among different tissues, and their anabolic pathways are highly conserved in plants [ 32 – 35 ]. And the metabolite species were not consistent with previous studies, which may be due to the different species of gardenia, suggesting that the genotype plays a decisive role in its metabolite species [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…Mulberry leaves contain polysaccharides, flavonoids, alkaloids, volatile oils, and other active components with hypoglycemic, hypolipidemic, antioxidant, anti-aging, and other effects [8][9][10][11]. In China, mulberry leaf has been clinically used as a traditional Chinese medicine for thirst (equivalent to diabetes in modern medicine) since ancient times [12]. Many scholars at home and abroad have reported on diabetes treatment with mulberry leaves, mostly focusing on the hypoglycemic effect of polysaccharides and flavonoids in mulberry leaves [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, MLs harvested after the initial frost are typically reserved for medicinal applications. The content of flavonoids in MLs reaches its peak during the period following the first frost and extending into November [ 8 ]. Additionally, another study investigated the correlation between the accumulation of total flavonoids and ambient temperature, suggesting that lower temperatures promote the accumulation of flavonoid compounds [ 9 ].…”
Section: Introductionmentioning
confidence: 99%